2014
DOI: 10.1016/j.jamda.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Inappropriate Prescribing of Antipsychotic Medications in People With Dementia Resident in Care Homes: A Systematic Review

Abstract: Interventions to reduce inappropriate prescribing of antipsychotic medications to people with dementia resident in care homes may be effective in the short term, but longer more robust studies are needed. For prescribing levels to be reduced in the long term, the culture and nature of care settings and the availability and feasibility of nondrug alternatives needs to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 45 publications
1
116
0
1
Order By: Relevance
“…However, to effectively improve the quality of life of a person with dementia, strategies that aim to reduce antipsychotic prescribing, such as medication reviews, need to be combined with evidence‐based non‐pharmacological interventions . A systematic review of the effectiveness of interventions to reduce inappropriate prescribing of antipsychotic medications in people with dementia living in residential care settings identified that for long‐term reduction in antipsychotic prescribing, interventions needed to address cultural issues and the poor availability of non‐drug alternatives to antipsychotics . It is clear that if an intervention is to achieve a long‐term reduction in psychotropic prescribing in dementia, it must provide options for practical, implementable, non‐resource intensive approaches to non‐pharmacological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, to effectively improve the quality of life of a person with dementia, strategies that aim to reduce antipsychotic prescribing, such as medication reviews, need to be combined with evidence‐based non‐pharmacological interventions . A systematic review of the effectiveness of interventions to reduce inappropriate prescribing of antipsychotic medications in people with dementia living in residential care settings identified that for long‐term reduction in antipsychotic prescribing, interventions needed to address cultural issues and the poor availability of non‐drug alternatives to antipsychotics . It is clear that if an intervention is to achieve a long‐term reduction in psychotropic prescribing in dementia, it must provide options for practical, implementable, non‐resource intensive approaches to non‐pharmacological strategies.…”
Section: Discussionmentioning
confidence: 99%
“…At the outset of the review, we developed an a priori logic model (Rohwer et al, ) to hypothesise how robopets might influence the health and well‐being of care home residents, staff and family members. The initial logic model was developed by the author team using theoretical literature (Beetz, ; Bernabei et al, ; Chur‐Hansen, Stern, & Winefield, ) and our experience of other reviews in the care home setting (Abbott et al, ; Thompson Coon et al, ; Whear et al, ). We considered the nature of the robopet intervention, the factors that may act as barriers to residents interacting with a robopet, the immediate outcomes (perceived and measured) for the resident and possible mediating factors (see Figure a) (Anderson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This review also noted a dose-dependent increase in somnolence, falls, infections and fever in those treated with antipsychotics. It has been argued that many institutionalized AD patients who are prescribed antipsychotics, are prescribed inappropriately, and educational programs to aid care workers in management of BPSD can reduce their use (Thompson Coon et al 2014). …”
Section: Bpsd and Ad Progressionmentioning
confidence: 99%